Article RETRACTED due to manipulation by the authors Endurance training and its impact on physical health among university students - Ardo Okilanda; Siti Ayu Risma Putri; Mutiara Fajar; Mario Febrian; Mardepi Saputra; Singha Tulyakul; Twinkle Duwarah; Aidil Putra; Baharuddin Hasan; Mudayat Mudayat; Wuri Syaputri (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study seeks to emphasise the importance of endurance training in improving the physical well-being of college students. Cardiovascular fitness, body composition, and muscular strength are crucial for overall health, particularly among university students, driving the motivation for this study. The study involved 42 university students who were surveyed using standardised instruments to evaluate their participation in endurance training activities and self-reported physical health indicators. Researchers conducted correlation studies to explore the connections between the frequency and duration of endurance exercise and cardiovascular fitness, body composition, and muscular strength. The study design involved survey distribution, data collection on physical health indicators, and statistical analysis to identify the correlations. The study's findings show that there are strong positive connections between the frequency and length of endurance training and improvements in cardiovascular fitness and muscular strength among university students. Nevertheless, there were no notable correlations found between body mass index and sit-up ability. These findings highlight the potential advantages of regular endurance training for improving various areas of physical health in this particular group. This study holds significance for coaches, fitness professionals, and university students. The significance of incorporating endurance training into the exercise regimens of university students to enhance their physical well-being is emphasised. Coaches can empower students to improve their overall well-being by emphasising the advantages of endurance exercise and offering personalised advice. This research further enhances the existing knowledge on the significance of endurance training in university settings by providing practical suggestions for coaching interventions.